Self-management strategies and care needs of patients with persistent depressive disorder and their informal caregivers: a multi-perspectives qualitative interview study - Ericka C. Solis; Ingrid V. E. Carlier; Noëlle G. A. Kamminga; Noëlle G. A. Kamminga; Albert M. van Hemert (Frontiers in Psychiatry)
IntroductionWhen patients with persistent depressive disorder (PDD) respond insufficiently to available evidence-based treatments, depression treatment guidelines recommend psychiatric rehabilitation through self-management. Preferably, the intervention should involve the patient’s informal caregiver.MethodsTo gain insight into the healthcare needs of PDD patients and their caregivers and to facilitate the implementation of a self-management program, we conducted individual semi-structured interviews with 28 PDD patients and 9 informal caregivers regarding their self-management/coping and needs. Transcripts were analyzed with Grounded Theory using three sensitizing concepts (PDD experience, self-management/coping, needs).ResultsPatients had 9 main themes and caregivers had 11 main themes. Patients and caregivers shared 9 main themes, pertaining to powerlessness, patients’ identity changes, shame/stigma, relationship dissatisfaction, family suffering, self-management attitudes, self-management strategies, coping support, and coping complications. While self-management attitudes of patients were mixed, those of caregivers were positive. Care needs of both groups centered on psychoeducation and communication skills development. Caregivers reported urgently needing support in dealing with patients’ suicidal behavior.DiscussionOur findings underscore the profound burden of PDD on both patients and their informal caregivers. We strongly recommend that healthcare professionals encourage and facilitate the development of self-management in depressed patients early in the treatment process and involve informal caregivers, particularly within suicide prevention strategies.Clinical Trial Registrationhttps://onderzoekmetmensen.nl/en/trial/55681, Netherlands Trial Register Identifier NL5818.